Evaluation of Phyto-active compounds, antioxidant, and antibacterial Efficacy of ethnomedicinal plants used by Manipuri tribe in Bangladesh: Phytochemical, Antioxidant, and Antibacterial Potential of Manipuri P - Sinha, Shiuly; Ahmed, Sheikh Rashel; Hossain, Ferdaus Mohd Altaf; Zinnah, Kazi Mohammad Ali (Journal of the Sylhet Agricultural University, 2026)
The present study aimed to investigate the medicinal properties (phytochemical screening, antioxidant potentiality, and antibacterial activity) of seven plant species used by the Manipuri tribe in Bangladesh. Most extracts showed effective antimicrobial activity against the tested pathogenic species and doses of minimum inhibitory concentration of plant extracts ranged from 12.5 μg/mL to 100 μg/mL. When compared to seven medicinal plants, the crude extract of Melastonia malabathricum and Oxalis corniculata exerted best minimum inhibitory doses against all studied bacterial (Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Salmonella sp and Staphylococcus aureus). Both Oxalis corniculata and Melastoma malabathricum showed best performance against Salmonella sp. Aerva sanguinolenta exhibited good performance to retard the growth of Staphylococcus aureus, Pseudomonas spp, and Escherichia coli. Furthermore, four medicinal plants (Oxalis corniculata, Aerva sanguinolenta, Melastoma malabathricum, and Mikania scandens) displayed potential activity against E. coli growth. The results of the phytochemical screening revealed that the extracts of plants (Houttuynia cordata, Oxalis corniculata, Leucas aspera, Mikania scandens, Aerva sanguinolenta, Spilanthes acmella, Melastoma malabathricum) contained alkaloids, steroids, phenols, proteins, flavonoids, saponins, amino acids, coumarins, and other compounds. The presence of phytochemicals varied from plant to plant. The methanolic extract of Houttuynia cordata contained the highest amount of total phenolic compounds, measuring 94.53 ± 0.45 mg/g gallic acid equivalent (GAE) of dry leaf powder. High total flavonoid content was found in the ethanolic crude extract of Melastoma malabathricum, with 78.76 ± 0.67 mg/g quercetin equivalent (QE) of dry leaf powder. The ethanolic and methanolic extracts of Melastoma malabathricum showed the highest total tannin content, 51.20 ± 0.09 and 50.50 ± 0.17 mg/g tannic acid equivalent (TAE) of dry leaf powder, respectively. Houttuynia cordata, Melastoma malabathricum, and Oxalis corniculata extracts exhibited potent antioxidant activity. To extend the current study, in vivo models are needed to prove the effectiveness of leaves as alternative drugs. J. Sylhet Agril. Univ. 12(2): 17-32, 2025